The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2174/1570180816666181129125511
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Inflammation with Conjugated Cinnamic Amides, Ethers and Esters

Abstract: Background: Cinnamic acid is a key intermediate in shikimate and phenylpropanoid pathways. It is found both in free form, and especially in the form of esters in various essential oils, resins and balsams which are very important intermediates in the biosynthetic pathway of several natural products. The cinnamic derivatives play a vital role in the formation of commercially important intermediate molecules which are necessary for the production of different bioactive compounds and drugs. Different substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In the present study, the new 3,4-disubstituted pyrrole derivatives and pyrrolecinnamate hybrids were evaluated in vitro for their antioxidant activity and their ability to inhibit soybean lipoxygenase and cyclooxygenase-2, in comparison to the well-known reference compounds trolox, nordihydroguaiaretic acid (NDGA) [30], and indomethacin [51]. For the sake of comparison, the previously published results of 4, 8 [31], 9 [27], and cinnamic acid's biological data [30] are also included (Table 2) The biological results are discussed in relation to the physicochemical properties of the molecules, e.g., the molecular volume (MV) and molar refractivity (MR) of the aromatic substituents Ar 1 and Ar 2 and ClogP and R M values.…”
Section: Biological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the new 3,4-disubstituted pyrrole derivatives and pyrrolecinnamate hybrids were evaluated in vitro for their antioxidant activity and their ability to inhibit soybean lipoxygenase and cyclooxygenase-2, in comparison to the well-known reference compounds trolox, nordihydroguaiaretic acid (NDGA) [30], and indomethacin [51]. For the sake of comparison, the previously published results of 4, 8 [31], 9 [27], and cinnamic acid's biological data [30] are also included (Table 2) The biological results are discussed in relation to the physicochemical properties of the molecules, e.g., the molecular volume (MV) and molar refractivity (MR) of the aromatic substituents Ar 1 and Ar 2 and ClogP and R M values.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…For the sake of comparison, the previously published results of 4, 8 [31], 9 [27], and cinnamic acid's biological data [30] are also included (Table 2) The biological results are discussed in relation to the physicochemical properties of the molecules, e.g., the molecular volume (MV) and molar refractivity (MR) of the aromatic substituents Ar 1 and Ar 2 and ClogP and R M values. to inhibit soybean lipoxygenase and cyclooxygenase-2, in comparison to the well-known reference compounds trolox, nordihydroguaiaretic acid (NDGA) [30], and indomethacin [51]. For the sake of comparison, the previously published results of 4, 8 [31], 9 [27], and cinnamic acid's biological data [30] are also included (Table 2) The biological results are discussed in relation to the physicochemical properties of the molecules, e.g., the molecular volume (MV) and molar refractivity (MR) of the aromatic substituents Ar 1 and Ar 2 and ClogP and RM values.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…A new series of synthetic cinnamic acid derivatives (Figure 3) incorporating a nitro group were evaluated as anti-inflammatory and antioxidant agents by Fotopoulos et al [34]. The new molecules tested as possible inhibitors of soybean LOX and ovine COX-2.…”
Section: Nitro-oxy Ester Hybrids As Anti-inflammatory and Antioxidant Agentsmentioning
confidence: 99%
“…In light of the above, continuing our efforts in the design of cinnamic hybrids [5], we report the synthesis of a new cinnamic acid-glycine hybrid combining two pharmacophore units in a single molecule. Earlier studies [6] showed that (E)-(3-(4-((4-bromobenzyl)oxy)…”
Section: Introductionmentioning
confidence: 98%